Characterization of the Myocarditis during the worst outbreak of dengue infection in China. Issue 27 (July 2016) - Li, Yingying; Hu, Zhongwei; Huang, Yuli; Li, Jianping; Hong, Wenxin; Qin, Zhihui; Tong, Yuwei; Li, Jinglong; Lv, Mingfang; Li, Meiyu; Zheng, Xiaoke; Hu, Jun; et al.
Abstract : Abstract: Myocarditis is a common complication of severe dengue infection. However, data about prevalence and characterization of myocarditis in dengue are still lacking. In 2014, the worst outbreak of dengue in the last two decades in China occurred. In this study, we described the clinical and laboratory diagnostic features of dengue with myocarditis. Totally, 1782 diagnosed dengue patients were admitted from August to October, 2014, all of whom were subjected to electrocardiogram, ultrasound cardiogram, and cardiac enzyme test. About 201 cases of dengue patients were diagnosed with myocarditis and the prevalence of myocarditis in hospitalized dengue was 11.28%. The prevalence of myocarditis in nonsevere dengue with warning signs and severe dengue [NSD(WS+)/SD] and nonsevere dengue without warning signs [NSD(WS–)] was 46.66% and 9.72%, respectively. The NSD(WS+)/SD patients with myocarditis presented with higher incidence of cardiac symptoms, supraventricular tachycardia (14.29% vs. 0%, P < 0.001), atrial fibrillation (25.71% vs. 10.24%, P = 0.019) and heart failure compared with NSD (WS–) patients with myocarditis. About 150 cases of dengue patients without myocarditis in the same period of time in department of Cardiology were recruited as control group. The proportion of NSD(WS+)/SD in dengue patients with and without myocarditis was 17.41% and 2.53%, respectively. Dengue patients with myocarditis experienced longer hospital stay than those without myocarditis (7.17 ± 4.64 vs. 5.98 ± 2.69, P = 0.008). There was no difference between patients with and without myocarditis in the proportion of symptoms, auxiliary methods abnormality, arrhythmia, and heart failure on the discharge day. Our study demonstrates the prevalence of myocarditis in worst outbreak of dengue in China was 11.28% and the incidence of myocarditis increased with the severity of dengue. The NSD(WS+)/SD patients with myocarditis presented with higher incidence of cardiac complication compared with NSD (WS–) patients with myocarditis. The prognosis of dengue patients with and without myocarditis had no significant difference even if myocarditis patients experienced longer hospital stay.